2021
DOI: 10.4236/jep.2021.1211054
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Chemical Toxicants in Waterpipe Tobacco and Waterpipe Charcoal Solid Waste

Abstract: This work provides insights on waterpipe tobacco and waterpipe charcoal as potential sources of environmental toxicants. Selected harmful and potentially harmful constituents (HPHCs) from ten U.S. commercial waterpipe tobacco filler products (before and after electric heating) and five waterpipe charcoal products (before and after burning) were investigated. The differences in quantities of HPHCs between the evaluated products appear to be affected by raw material properties and/or the manufacturing processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Furthermore, the smoke from one session of water pipe smoking exposes an individual to about 40 times the tar and 10 times the carbon monoxide compared to a single cigarette [26] A toxicological study comparing inhaled toxicants from cigarettes and water pipes also found that one session of water pipe smoking is associated with about 74 litres of smoke, compared to a single cigarette that is associated with about 0.6 litres of smoke [26] . It has been shown that using water as a filter during water pipe smoking did not change the level of nicotine in the smoke [39] which could lead to nicotine dependence. It is described how a single water pipe session produces a nicotine level equivalent to 10 cigarettes per day in a 24hour urine specimen [12] However, in order to understand the quantity of nicotine that the user might be exposed to, it should be remembered that a single puff of water pipe smoking has more volume compared to cigarette smoking [26] .…”
Section: Risk Perception and Attitude Towards Water Pipe Smokingmentioning
confidence: 99%
“…Furthermore, the smoke from one session of water pipe smoking exposes an individual to about 40 times the tar and 10 times the carbon monoxide compared to a single cigarette [26] A toxicological study comparing inhaled toxicants from cigarettes and water pipes also found that one session of water pipe smoking is associated with about 74 litres of smoke, compared to a single cigarette that is associated with about 0.6 litres of smoke [26] . It has been shown that using water as a filter during water pipe smoking did not change the level of nicotine in the smoke [39] which could lead to nicotine dependence. It is described how a single water pipe session produces a nicotine level equivalent to 10 cigarettes per day in a 24hour urine specimen [12] However, in order to understand the quantity of nicotine that the user might be exposed to, it should be remembered that a single puff of water pipe smoking has more volume compared to cigarette smoking [26] .…”
Section: Risk Perception and Attitude Towards Water Pipe Smokingmentioning
confidence: 99%
“…Recent epidemiological research has shown that tobacco consumption by waterpipe has negative effects on human health, including esophageal cancer, lung and oral cancers, infectious diseases, impaired respiratory function, cardiovascular disease, low birth weight, and dental problems [ 4 , 12 , 13 ]. The increasing trend of waterpipe smoking not only provides risks to more people who smoke but may also lead to increased environmental pollution from the disposal of waterpipe tobacco wastes (WTWs) [ 10 , 14 ]. Unlike the waste from discarded cigarettes, toxic chemicals from WTWs can be released into the aquatic and terrestrial environments through waste produced from different parts of the waterpipe system [ 12 ].…”
Section: Introductionmentioning
confidence: 99%